2017
DOI: 10.1590/0103-6440201701481
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hemostatic Solution on Bond Strength and Physicochemical Properties of Resin Cement

Abstract: The aim of this study was to evaluate the degree of conversion, color stability, chemical composition, and bond strength of a light-cured resin cement contaminated with three different hemostatic solutions. Specimens were prepared for the control (uncontaminated resin cement) and experimental groups (resin cement contaminated with one of the hemostatic solutions) according to the tests. For degree of conversion, DC (n = 5) and color analyses (n = 10), specimens (3 mm in diameter and 2 mm thick) were evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The present study showed statistical differences between the cement tested in both light sources, but none had DC% lower than acceptable values in other studies [21,22]. Besides color stability, it should be highlighted that the longevity of the cemented ceramic restorations also depends on the correct cementation technique, with proper control of humidity using dental isolation [23,24], control of gingival bleeding during cementation [25], and proper removal of resin cements excesses [26]. 3.…”
Section: Discussionmentioning
confidence: 49%
“…The present study showed statistical differences between the cement tested in both light sources, but none had DC% lower than acceptable values in other studies [21,22]. Besides color stability, it should be highlighted that the longevity of the cemented ceramic restorations also depends on the correct cementation technique, with proper control of humidity using dental isolation [23,24], control of gingival bleeding during cementation [25], and proper removal of resin cements excesses [26]. 3.…”
Section: Discussionmentioning
confidence: 49%
“…The cleansing efficacy of some of these cleansing methods for the bond strength of some cements has been previously investigated [ 4 6 ]. However, the available literature on this topic is inconclusive [ 7 , 8 ]. Therefore, this study aimed to assess and compare the effect of various mechanical and chemical cleansing protocols on the bond strength of an etch-and-rinse adhesive to dentin contaminated with aluminum chloride hemostatic agent.…”
Section: Introductionmentioning
confidence: 99%